Phytotoxic effects of argan shell biochar on salad and barley germination - Bouqbis, Laila; Daoud, Salma; Koyro, Hans Werner; Kammann, Claudia Irene; Ainlhout, Fatima Zohra; Harrouni, Moulay Cherif (Agriculture and Natural Resources, 2017)
Biochar produced from argan shells can be contaminated by toxic substances accumulated during the pyrolysis process. To determine the potential impact of toxic substances and salt stress, this study focused on the effect argan shell biochar had on the germination of salad (0%, 0.5%, 1%, 2%, 4% or 8% biochar dry weight in a sand-biochar mixture) and barley seeds (0%, 1%, 2.5%, 5% or 10% biochar dry weight in a peat-biochar mixture). No negative salt stress effect of argan biochar on the germination of salad was observed nor on the germination rate and fresh weight of seedlings. Additionally, biochar application increased the germination rate and the fresh biomass weight in all of the treatments. No significant difference was observed from the control with the barley germination rate, fresh and dry weights of barley seedlings, water content and water use efficiency of different mixtures (peat-biochar). Thus, for both the salad and barley germination tests, no negative effects of biochar produced from argan shells were identified, providing a preliminary indication that it could be safely used for agriculture.